Spectrum of ocular manifestations and visual outcomes of neurosyphilis among 53 patients - Tatiana Vaz Leite Pinto; Antônio Pereira Gomes Neto; Matheus Nader Cunha; Letícia Moreira Bernardino; Paulo Pereira Christo (Arquivos de Neuro-Psiquiatria)
ABSTRACT Background: In the era of the re-emergence of syphilis, ocular syphilis has gained attention because its prevalence has increased and it can cause blindness and disability. Objectives: To investigate the clinical presentation and prognosis of ocular syphilis. Methods: Prospective study on 53 patients (90 eyes) with ocular syphilis diagnosed at the Santa Casa of Belo Horizonte, Brazil. The diagnosis was based on clinical manifestations of the disease and on serological markers (positive serum treponemal and non-treponemal tests or two positive treponemal tests). Results: Thirty-five eyes (66%) were from men and the mean age was 45.3 ± 12.0 years. HIV coinfection was confirmed in 10 patients (18.9%). Forty-four (84.9%) had VDRL titers ≥ 1:32. Bilateral ocular involvement occurred in 68%. Optic neuritis was diagnosed in 51.7% of the eyes and uveitis in 48.2%. Regarding visual acuity, the median baseline logarithm of the minimum angle of resolution (logMAR) was 1 (20/200 Snellen), while after antibiotic therapy, the median was 0.2 (20/30 Snellen). Poor visual acuity after treatment, defined as the best-corrected visual acuity (BCVA; logMAR 1; 20/200 Snellen) or worse, was associated with severe BCVA at presentation (below logMAR 1.3; 20/400 Snellen) (p = 0.001) and age over 50 years (p = 0.001). Conclusions: This study confirms the wide spectrum of clinical manifestations of ocular syphilis. The most frequent form was optic neuritis, an important differential diagnosis from other causes of inflammatory neuritis. Early diagnosis is essential, given that this is a treatable condition with excellent visual recovery in most cases.